Combined laryngeal inflammation and trauma mediate long-lasting immunoreactivity response in the brainstem sensory nuclei in the rat - Simonyan, Kristina; Feng, Xin; Henriquez, Victor; Ludlow, Christy (Frontiers in Integrative Neuroscience, 2012)
Somatosensory feedback from the larynx plays a critical role in regulation of normal upper airway functions, such as breathing, deglutition and voice production, while altered laryngeal sensory feedback is known to elicit a variety of pathological reflex responses, including persistent coughing, dysphonia and laryngospasm. Despite its clinical impact, the central mechanisms underlying the development of pathological laryngeal responses remain poorly understood. We examined the effects of persistent vocal fold (VF) inflammation and trauma, as frequent causes of long-lasting modulation of laryngeal sensory feedback, on brainstem immunoreactivity in the rat. Combined VF inflammation and trauma were induced by injection of lipopolysaccharide (LPS) solution and compared to VF trauma alone from injection of vehicle solution and to controls without any VF manipulations. Using a c-fos marker, we found significantly increased Fos-like immunoreactivity (FLI) in the bilateral intermediate/parvicellular reticular formation (IRF/PCRF) with a trend in the left solitary tract nucleus (NTS) only in animals with LPS-induced VF inflammation and trauma. Further, FLI in the right NTS was significantly correlated with the severity of LPS-induced VF changes. However, increased brainstem FLI response was not associated with FLI changes in the first-order neurons of the laryngeal afferents located in the nodose and jugular ganglia in either group. Our data indicate that complex VF alterations (i.e., inflammation/trauma vs. trauma alone) may cause prolonged excitability of the brainstem nuclei receiving a direct sensory input from the larynx, which, in turn, may lead to (mal)plastic changes within the laryngeal central sensory control.